A Model of Mathematical Problem Solving with Technology: The Case of Marco Solving-and-Expressing Two Geometry Problems - Carreira, Susana (2020)
Research has long been using analytical tools to describe the processes students engage in when solving non-routine mathematical problems. In this chapter we describe and discuss our progress on devising and implementing an analytical tool that aims to account for the use of technological tools by combining a mathematical problem solving model with a digital problem solving framework. By means of the Mathematical Problem Solving with Technology model (MPST) we report the case of Marco using technologies for solving two problems from a beyond school competition. Results show that Marco’s choice of the tools is grounded on an explicit knowledge of their affordances and how they enhance his mathematical thinking, mainly by triggering visual approaches that support the development of conceptual models for solving-and-expressing the solutions to the problems.